Упругость магнитного поля - Чашко, М. В. (НТУ "ХПИ", 2013)
The magnetic field can provide elasticity to the force transmission elements of mechanical systems. Elasticity is invariant to coordinate or non-linearly dependent on it, depending on the distance between the magnets. With non-linear elastic there fluctuations in the speed and the way.
Keywords: механические передачи; создание упругости; постоянные магниты; упругие элементы; снижение динамических нагрузок; стабилизация потребления мощности